Solon of Athens : Poet, Philosopher, Soldier, Statesman. - Owens, Ron (Liverpool University Press, 2010)
Addresses the historical, social and political contexts within which Solon of Athens instituted wide-ranging reforms to the Athenian constitution (594-93 BCE), the impact of those reforms on the political self-awareness of the archaic Athenians themselves, and the ethical and political philosophies that drove reform.